Pengaruh Servant Leadership dan Komunikasi Interpersonal terhadap Kinerja Aparatur Sipil Negara Melalui Organizational Citizenship Behavior - Yanti, Dhiana; Madris Madris, Madris; Ami Pujiwati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine the effect of servant leadership and interpersonal communication on ASN performance and organizational citizenship behavior (OCB), the effect of organizational citizenship behavior (OCB) on ASN performance, the effect of servant leadership and interpersonal communication on ASN performance through organizational citizenship behavior (OCB) at the BKKBN Representative Office of West Sulawesi Province. To obtain the required data, a questionnaire was distributed. The data analysis technique used smartpls 4.1.0.8. The results of the study showed that servant leadership can significantly improve organizational citizenship behavior, interpersonal communication has a significant effect on improving organizational citizenship behavior, servant leadership can significantly improve ASN performance, interpersonal communication can significantly improve ASN performance, organizational citizenship behavior can significantly affect ASN performance, organizational citizenship behavior can mediate the influence of servant leadership on ASN performance, organizational citizenship behavior can mediate the influence of interpersonal communication on ASN performance at the BKKBN office of West Sulawesi Province. The findings in this study indicate that personal communication can improve organizational citizenship behavior so that it has an impact on improving ASN performance at the BKKBN office of West Sulawesi Province